Pengaruh Tindakan Penagihan Pajak Melalui Surat Teguran, Surat Paksa dan Surat Penyitaan terhadap Pencairan Tunggakan Pajak di KPP Pratama Gianyar - Maria Trishanti Ina Ose; I Nyoman Gede Arya Diatmika (Pusat Riset dan Inovasi Nasional, 2026)
The high and fluctuating level of tax arrears at KPP Pratama Gianyar highlights the need to evaluate the effectiveness of tax collection actions. This study aims to analyze the influence of warning letters, forced letters, and seizure letters on the disbursement of tax arrears at KPP Pratama Gianyar during the period of January 2021–December 2024. This research employs a quantitative associative approach using secondary monthly data consisting of 48 observations obtained through total sampling. Data were analyzed using multiple linear regression, supported by classical assumption testing, t-test, F-test, and coefficient of determination. The results show that warning letters and forced letters have a positive and significant effect on the disbursement of tax arrears, while seizure letters do not have a significant effect. Simultaneously, the three tax collection variables significantly affect tax arrears disbursement, with an adjusted R² value of 43.9%. These findings emphasize the importance of strengthening collection strategies through warning and forced letters, as well as the need for further evaluation regarding the effectiveness of seizure letters as a final legal enforcement instrument.